Pengaruh Pendidikan Keuangan di Keluarga terhadap Perilaku Hidup Hemat (Frugal Living) Mahasiswa Universitas Sebelas Maret dengan Literasi Keuangan sebagai Variabel Intervening - Dea Camelia; Mintasih Indriayu; Sudarno Sudarno (Journal on Education, 2024)
This study aims to determine the effect of financial education in the family on frugal living behavior as mediated by financial literacy. The research method used is descriptive quantitative. The research method uses descriptive quantitative. The sampling technique uses purposive sampling with a sample of 293 UNS students consisting of the Faculty of Economics and Business (Development Economics, Accounting, Management) and the Faculty of Teacher Training and Education (Economic Education and Accounting Education). The data collection technique uses a questionnaire that has been tested for validity and reliability. This study uses data analysis techniques using path analysis (path analysis). The results of this study show that financial education in the family has a positive and significant influence on students' frugal living behavior, financial education in the family has a positive and significant influence on students' financial literacy, financial literacy has a positive and significant influence on students' frugal living behavior, and there is an influence Indirect financial education in the family towards frugal living behavior through financial literacy.